1991
DOI: 10.1029/91wr01369
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of a Liquid Front in an Unsaturated, Fractured Porous Medium

Abstract: We consider liquid infiltrating by gravity flow into a system of parallel, regularly spaced fractures in an unsaturated porous medium. The position of the fracture liquid front as a function of time, under some simplifying assumptions, is shown to obey a nonlinear integrodifferential equation. Approximate analytic solutions are developed, showing that the movement of the liquid front exhibits three major flow periods: (1) at early time, the frontal position is determined by the fracture inlet boundary conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 22 publications
0
47
0
2
Order By: Relevance
“…The results of the new method can also be compared to the asymptotic analytical solutions developed by Nitao and Buscheck [1991]. They treated the mathematically analogous problem of linearized capillary-driven flow into an unsaturated, fractured formation, and found the leading-order terms for the flux in each of the three time regimes.…”
Section: Coupled Dual-porosity Simulatormentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the new method can also be compared to the asymptotic analytical solutions developed by Nitao and Buscheck [1991]. They treated the mathematically analogous problem of linearized capillary-driven flow into an unsaturated, fractured formation, and found the leading-order terms for the flux in each of the three time regimes.…”
Section: Coupled Dual-porosity Simulatormentioning
confidence: 99%
“…Following their procedure, we can develop the asymptotic solutions for the present saturated flow problem. At small times the solution corresponds to flow into the fracture network with the matrix blocks assumed to be impermeable, which leads to a mass fiowrate of (38) In the late time regime, Nitao and Buscheck [1991] showed that the problem becomes asymptotically equivalent to one-dimensional flow into a porous formation whose permeability is essentially equal to k 1 (since km « k 1 ), but whose porosity is equal to <l>t +<l>m· Since the compressibility terms (which reflect only cwater) in both the matrix and fractures are equal, the late-time fiowrate is asymptotically wven by (39) J,. ; Nitao and Buscheck [1991, eq.…”
Section: Coupled Dual-porosity Simulatormentioning
confidence: 99%
“…There are two bounding cases: -A lower bound for flow velocity in the superheated environment is provided by assuming that flow is always fully developed and the saturation in the liquid finger remains at its initial value (i.e., S l = 1). (This scenario was used by Nitao and Buscheck [1991], studying liquid infiltration into a fracture under the influence of matrix imbibition.) Flow velocity in the liquid finger changes linearly with mass flow rate (v(z,t)/v P = m(z,t)/m P = k r ), which gives rise to a significant decrease of v(z,t) as vaporization becomes effective.…”
Section: Finger Flow Velocity Representationmentioning
confidence: 99%
“…Under these conditions, the speed of the wetting front in the fracture is governed by the competition between the driving forces in the fracture (gravity and fracture capillarity) and capillary imbibition into the matrix. Fracture-dominated flow can be classified into three physically interpretable flow periods [3,13], conesponding to the degree to which matrix interaction retards the speed of the wetLing front in the fracture, with minimal retardation occurring during flow period I, intermediate retardation during flow period II, and maximal retardation during flow period III (Fig. 2).…”
Section: Matrix-dominated Vs Fracture-dominated Flowmentioning
confidence: 99%